Emotional intelligence among homosexual of LGBT community - Mediana, Phycilicia Arsyane; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
We review studies on emotional intelligence among homosexual or Lesbian, Gay, Bisexual, Transgender and Transexual (LGBT) community. The literature were analyzed and organized according to the definitions of emotional inetelligence of homosexual, in particular Lesbian, Gay, Bisexual, Transgender and Transexual (LGBT) community in detail. We found that Freud thinks that everyone has a hidden homosexual tendencies. On the other hand, social learning theory, LGBT is due to socially acceptable behavior without being punished. There are two various kind of homosexuals, such as homosexual who can sync with their ego and who can not sync with their ego. In this review, we know that different kind of homosexual have different phases of emotional intelligence and identity formation. In conclusion, we then suggest for future interventional study to compare earlier phase and later phase intervention for homosexual emotional intelligence development.